Job stress, social comparison, orientation and effective responses to social comparison information among the bank employees in Kalibo, Aklan. - Reynaldo, Adorada
The study was conducted to describe the bank employees' levels of job stress, social comparison orientation, affective responses to social comparison and the relationship among some of these variables. The sample consisted of ninety (90) bank employees in Kalibo, Aklan selcted using sratified random sampling technique with proportionate allocation and with replacement. The data were gathered with the use of self-administered quationnaires mainly composed of scales. Data analyses employed were descriptive and correlational statistics. Results indicated that majority of the bank employees does not find their jobs higly stressful and most of them have strong dispositional need for social comparison; also, upward comparisn generated more positive affective response and moderate negative affective response while downward comparison was responded to with less negative affect and moderate positive affect. Results also provided support for the hypothesized relationships between social comparisons. However, the study did not lend support to the hypothesized relationships levels of job stress and the affective responses (positive and negative) to upward and downward comparsion, and between social comparison orientation and the positive affective dimension of upward comparison.
Research Study (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Employees, Bank -- Kalibo, Aklan